2016
DOI: 10.15376/biores.11.4.8269-8276
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Important Factors for Xylanase and Cellulase Production from the Fungus C. cinerea RM-1 NFCCI-3086 through Plackett-Burman Experimental Design

Abstract: A Plackett-Burman design was employed to evaluate the effect of different culture conditions associated with xylanase and cellulase production by the fungus C. cinerea RM-1 NFCCI 3086 using agro-residues as substrate. Eight variables were assessed for their significance on xylanase and cellulase production under solid state fermentation. The optimal culture conditions for xylanase production were developed by maintaining the variables of temperature, incubation period, substrate concentration, particle size, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It has been reported that moisture content more than the optimal value decreased the porosity which results into decreased availability of required oxygen for the growth and development of aerobic microorganisms. On another side, lower moisture level than the optimal level reduced the swelling of the substrate and resulted into difficult nutrient transfer (Maan et al 2016;Kar et al 2013). Ghoshal et al (2012Ghoshal et al ( , 2015 obtained higher endoxylanase production at 1:5 solid-to-moisture ratio on 5th day of incubation by P. citrinum MTCC 9620 and P. citrinum MTCC 2553, respectively.…”
Section: Optimization Of Culture Conditions In Ssfmentioning
confidence: 99%
“…It has been reported that moisture content more than the optimal value decreased the porosity which results into decreased availability of required oxygen for the growth and development of aerobic microorganisms. On another side, lower moisture level than the optimal level reduced the swelling of the substrate and resulted into difficult nutrient transfer (Maan et al 2016;Kar et al 2013). Ghoshal et al (2012Ghoshal et al ( , 2015 obtained higher endoxylanase production at 1:5 solid-to-moisture ratio on 5th day of incubation by P. citrinum MTCC 9620 and P. citrinum MTCC 2553, respectively.…”
Section: Optimization Of Culture Conditions In Ssfmentioning
confidence: 99%
“…It has been shown that moisture level higher than optimal value results in reduced porosity which further lowers the availability of oxygen required for the growth of aerobic microorganism. On the other hand, the moisture content lower than optimal level reduces the swelling of the substrate which makes transfer of nutrients difficult (Kar et al, 2013;Maan, Bharti, Gautam, & Dutt, 2016;Raimbault & Alazard, 1980). Gao et al (2008) reported maximum endoglucanase and FPase production by Aspergillus terreus M11 at 80% of moisture content using corn stover as the substrate under SSF.…”
Section: Effect Of Moisture Contentmentioning
confidence: 99%
“…In this study, the effectiveness of pretreatment methods was correlated with the titers of xylanase obtained from the fermentation of pretreated SB by B. aestuarii UE25. The factors affecting xylanase production on pretreated SB were evaluated by a statistical method, PBD, that was found to be an effective tool to improve the production of microbial enzymes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%